2020
DOI: 10.3390/su12145663
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Assessment and Engineering of Emerging Aircraft Technologies—Challenges, Methods and Tools

Abstract: Driven by concerns regarding the sustainability of aviation and the continued growth of air traffic, increasing interest is given to emerging aircraft technologies. Although new technologies, such as battery-electric propulsion systems, have the potential to minimise in-flight emissions and noise, environmental burdens are possibly shifted to other stages of the aircraft’s life cycle, and new socio-economic challenges may arise. Therefore, a life-cycle-oriented sustainability assessment is required to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…For instance, bauxite was very recently included in the European Commission's critical raw materials list [46]. Furthermore, environmental emissions were found to be affected by the flight altitude; e.g., in [47]. In this direction, reliable models to assess the overall impact on the climate, under a comprehensive life cycle study, are required; however, such investigations lie outside the scope of the present work.…”
Section: Environmental and Economic Impact Comparisonmentioning
confidence: 99%
“…For instance, bauxite was very recently included in the European Commission's critical raw materials list [46]. Furthermore, environmental emissions were found to be affected by the flight altitude; e.g., in [47]. In this direction, reliable models to assess the overall impact on the climate, under a comprehensive life cycle study, are required; however, such investigations lie outside the scope of the present work.…”
Section: Environmental and Economic Impact Comparisonmentioning
confidence: 99%
“…These include hybrid-electric concepts [34], universal-electric powered concepts [35], or the use of Sustainable Aviation Fuels (SAFs) [36,37]. For these future technologies, a prospective LCA can be helpful for decision support in the design process or during engineering [38]. Johanning and Scholz [39], who compared electric, Liquid Hydrogen (LH 2 ), and SAF-powered aircraft, further indicated that additional renewable energy sources will be required to meet the increased energy demands of these concepts.…”
Section: Life Cycle Assessment In Aviationmentioning
confidence: 99%
“…These studies emphasize the influence of the battery on aircraft sustainability. Moreover, a doubling of the battery's specific energy compared to the state‐of‐the‐art would be required to make electric flying viable on short‐haul flights (Gnadt et al., 2019; Melo, Cerdas et al., 2020; Schäfer et al., 2019). Simultaneously, the electricity mix for recharging the battery affects the environmental impacts significantly.…”
Section: Introductionmentioning
confidence: 99%